ASSOCIATION BETWEEN THE BASELINE GENE EXPRESSION PROFILE IN PERIAPICAL GRANULOMA AND PERIAPICAL WOUND HEALING AFTER SURGICAL ENDODONTIC TREATMENT - Ahmed, Muhammad Adeel; Nazim, Fizza; Ahmed, Khalid; Bari, Muhammad Furqan; Abdulwahed, Abdulaziz; AlMokhatieb, Ahmed A; Alalvi, Yaseen; Abduljabbar, Tariq; Mughal, Nouman; Abidi, Syed Hani (Scientifc Reports, 2022)
In this study, we have investigated the association between the baseline gene expression profile in periapical granuloma and periapical wound healing after surgical endodontic treatment. Twenty-seven patients aged between 15 and 57 years underwent periapical surgery. The retrieved periapical tissue sample was used for mRNA expression analysis of COL1A1, VTN, ITGA5, IL-4, TNF, ANGPT, VEGFA, and CTGF. All patients were recalled after 6 and 12 months for periapical healing evaluation. Healing was then correlated with baseline gene expression. Healing was observed in 15 patients at the end of 6 months, which increased to 21 patients after 12 months. Six patients showed no healing even after 12 months. Analysis of baseline expression levels of the tested genes with healing status showed the mean relative expression of VTN, VEGFA, ANGPT, TNF, and CTGF to be significantly different (p < 0.05) between the healing group (6 and 12 months) (72.99%) and the non-healing (94.42%) group. Periapical Index scores 3–5 exhibited a positive correlation with ITGA-5 expression. Overexpression of ANGPT and a strong positive correlation between ITGA5 and PAI scores in the non-healing group of patients may suggest these genes to be a potential prognostic biomarker for periapical wound non-healing after surgical endodontic treatment.
Keywords: Type of access: Open Access; baseline gene expression; periapical granuloma; surgical endodontic treatment